2009
DOI: 10.1007/s10750-009-9839-0
|View full text |Cite
|
Sign up to set email alerts
|

The new threat to Italian inland waters from the alien crayfish “gang”: the Australian Cherax destructor Clark, 1936

Abstract: Biological invasions inflict damage to the ecology, economy, and human health, and pose serious threats to the native communities. Among the many invasive taxa, crayfish have attracted much attention by scientists and policy makers. Recently, an established population of an alien species of crayfish, new for Italy, was found in the Natural Preserve of ''Laghi di Ninfa'' (central Italy). Based on morphological and genetic evidence (molecular barcoding of COI and 16S rDNA), we classified it at subspecies level a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 27 publications
0
28
0
1
Order By: Relevance
“…Since the early 1990s, both yabby and redclaw (C. destructor and C. quadricarinatus, respectively) are intensively farmed in Italy (D'Agaro et al, 1999). Scalici et al (2009) reported an established population in the Natural Preserve of "Laghi di Ninfa" (central Italy). The animals were probably introduced at the end of the 1980s to foster an experimental aquaculture.…”
Section: > Cherax Destructor Clark 1936; Yabby (Figure 9)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the early 1990s, both yabby and redclaw (C. destructor and C. quadricarinatus, respectively) are intensively farmed in Italy (D'Agaro et al, 1999). Scalici et al (2009) reported an established population in the Natural Preserve of "Laghi di Ninfa" (central Italy). The animals were probably introduced at the end of the 1980s to foster an experimental aquaculture.…”
Section: > Cherax Destructor Clark 1936; Yabby (Figure 9)mentioning
confidence: 99%
“…Advances in astacological research since the publication of the Atlas allowed filling at least some of these gaps (e.g., Trožić-Borovac, 2011;Simić et al, 2008), and also led to re-assessment of species identity and diversity of some of the alien species present in European waters (e.g., Chucholl and Daudey, 2008;Filipová et al, 2011). Furthermore, expansion of invasive species was well documented for some regions e.g., Italy (Aquiloni et al, 2010) and Romania (Pârvulescu et al, 2009, and isolated populations of various recently introduced alien species were discovered in many European countries (e.g., Scalici et al, 2009;Jaklič and Vrezec, 2011;Chucholl et al, 2012). Some of these changes that became known since the publication of the Atlas were reflected in the comprehensive review by , which nevertheless re-used the original 2006 maps.…”
Section: Introductionmentioning
confidence: 99%
“…This 'centrality' makes P. antennarius a more imperiled taxon if we also consider the introduction and spreading of both alien invertebrates and fish species as potential competitors and/or predators This may be the case for very stressed areas such as in central Italy where diverse invasive crayfish (Chiesa et al, 2006;Nonnis et al, 2009;Scalici et al, 2010Scalici et al, , 2009bScalici et al, , 2009cDörr and Scalici, 2013;Bissattini et al, accepted) and their unsafe parasites (Dörr et al, 2011(Dörr et al, , 2012a(Dörr et al, , 2012bChiesa et al, 2015) were recorded and described. Scientists are often expected to indicate the most important species which disturbance may originate the main detrimental effect on both occurrence and abundance of other taxa in a community (Jones et al, 1994).…”
Section: Familymentioning
confidence: 99%
“…In Italy several non-native crayfish have been recorded (Souty-Grosset et al, 2006;Capurro et al, 2007;Gherardi et al, 2008b): (a) three American species, the red-swamp crayfish Procambarus clarkii (Girard, 1852), the spiny-cheek crayfish Orconectes limosus (Rafinesque, 1817), and the signal crayfish Pacifastacus leniusculus (Dana, 1852); (b) two Australian species, the yabby Cherax destructor (Clark, 1936), and the redclaw C. quadricarinatus (von Martens, 1868); (c) one eastern European species, the narrow-clawed crayfish Astacus leptodactylus (Eschscholtz, 1823). C. quadricarinatus was only observed in rearing systems , whilst C. destructor was recently recorded in abandoned outdoor ponds within the protected area "Laghi di Ninfa" (Latina, Latium) (Scalici et al, 2009a Chiesa et al, 2006), and C. destructor (Scalici et al, 2009a). On the whole, NICs show a wide distribution due to their ability to adapt to a wide range of habitat and food sources, especially P. clarkii (Gherardi, 2006;Scalici et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%